(untitled) (New York, 1980)
The book is organized into six parts. Parts one and two are concerned with basic statistical models nad basis for inference, that is, the tools of econometric analysis. Parts three and four recognize the dynamic, stochastic, and heterogeneous nature of economic data and consider statistical models consistent with these data generation processes. Part five is concerned with statistical models that recognizethat much economic data are generated by systems of relations that are dynamic, stochastic, and simultaneous. Part six recognizes that (1) some economic variables are either nonobservable or measured with error, (2) some economic variables are discrete rather than continuous, (3) some economic parameters are stochstic or variable rather than fixed, (4) not all random variables of interest are normally distributed, (5) not all statistical models used in practice have design matrices with correct column dimension and finally, (6) some design matrices are ill conditioned. Three appendices to the book are concerned with (1) matrix and distribution theorems that are used throughout the book, (2) numerical optimization methods that provide a computational base for a range of nonlinear models considered throughout the book and (3) Kalman filter models that provide a rather general framework for handling a range of economic models
Keywords: Econometrics,Economics, mathematical